2021
DOI: 10.1002/onco.13802
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Prognostic Factors of Patients with Metastatic Colorectal Cancer Who Underwent Pulmonary Metastasectomy with Curative Intent: A Brazilian Experience

Abstract: Background. We aimed to identify clinicopathological and molecular features associated with progression-free survival (PFS) and overall survival (OS) after pulmonary metastasectomy for metastatic colorectal cancer in a retrospective cohort in Brazil. Materials and Methods. We did a retrospective review of thoracic surgeries performed in a single large academic hospital in Brazil from January 1985 to September 2019. Demographics, previously described prognostic factors, and clinicopathological and molecular cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(49 reference statements)
1
8
1
Order By: Relevance
“…Our study found a five-year OS of 33.2%, which is within the range of OS in such cases described in the literature (27%-68%) (5). Nevertheless, it is far from the 49.8% found by Gössling in Brazil (8) and even further from the 68.1% described by Okumura in Japan (9). Our OS was similar to that reported in the PulMiCC trial (NCT01106261), the only randomized controlled trial to date comparing pulmonary metastasectomy with systemic therapy, which reported a 38% five-year survival for metastasectomy and was stopped due to poor recruitment (10).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our study found a five-year OS of 33.2%, which is within the range of OS in such cases described in the literature (27%-68%) (5). Nevertheless, it is far from the 49.8% found by Gössling in Brazil (8) and even further from the 68.1% described by Okumura in Japan (9). Our OS was similar to that reported in the PulMiCC trial (NCT01106261), the only randomized controlled trial to date comparing pulmonary metastasectomy with systemic therapy, which reported a 38% five-year survival for metastasectomy and was stopped due to poor recruitment (10).…”
Section: Discussionsupporting
confidence: 72%
“…In our series, the five-year DFS was slightly below this range (21.6%) probably due to the factors described above. Nevertheless, it should be noted that the median DFS was 24.6 which was higher than the median DFS of 14 months (95% CI, 10.4-17.5) described by Gössling et al (8), in their study that included 58 patients who underwent pulmonary metastasectomy from CRC in Brazil.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…At present, simultaneous surgical resection has become an optional treatment option for CRC patients with LM or PM. The lack of cytokeratin 20 expression in metastases is associated with poor overall survival for CRC PM patients ( 30 ). Isolated unilateral lung metastasis with normal CEA levels and no lymph node involvement is a positive prognostic factor for patients ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to the metastases of other primary tumours. These risk factors are equally effective in colorectal cancer metastasis surgery (liver metastases [283][284][285][286][287][288][289]; pulmonary metastases [290][291][292][293]). Thus, after clinical R0 resection of organ metastases, a large number of studies show that both the overall tumour burden (singular/multiple metastases, size or number of metastases) and growth rate dependent factors (synchronous/metachronous metastases, interval to onset) influence the outcome.…”
Section: Ispmrcc and Risk Factorsmentioning
confidence: 99%